Aplikasi Pembelajaran Alfanumerik Untuk Anak Usia Pra-Sekolah Berbasis Android Menggunakan Metode Tesseract-Ocr - Darmawan Aditama; Harunur Rosyid; Nuniek Fahriani (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2018)
Alphanumeric writing ability is the main provision for children to be able to understand the subjects given in school. One alternative to help increase children's interest and ability in learning to write Alphanumeric is to use learning media in the form of software. This study is to create an application that presents Alphanumeric writing learning that is intentionally packaged in the form of a game in order to increase the learning interest of pre-school age children. In this study used the method of recognition of character letters made by the player. In character recognition, the application will record the handwriting that the user has created on the board provided. The handwriting will then be used at the image processing stage that uses Tesseract as the recognition engine. And from the results of the trials, pre-school children easily manage it.